Atmospheric SO2 oxidation by NO2 plays no role in the mass independent sulfur isotope fractionation of urban aerosols. (November 2018) - Au Yang, D.; Bardoux, G.; Assayag, N.; Laskar, C.; Widory, D.; Cartigny, P.
Abstract: Modern anthropogenic aerosols usually exhibit low but significant Δ 33 S signatures (−0.6 to 0.5‰) whose origin still remains unclear. While isotope fractionation factors associated with the oxidation of SO2 by O2 +TMI (Transition Metal Ion), H2 O2 or OH cannot lead to such extreme Δ 33 S-values, an increasing number of studies points to the significant role of NO2 as a contributing oxidant, especially in the urban environment. To address the possible relation between atmospheric NO2 and observed Δ 33 S-values in aerosols, we carried out laboratory experiments oxidizing SO2 by NO2 at temperatures ranging between −7 and 52 °C. Our results show that at temperatures ≥10 °C SO2 oxidation by NO2 is characterized by 1) a 34 α-value whose temperature dependence (0.2437/T+0.0457) is distinct from those related to oxidation by O2 +TMI, H2 O2 and OH oxidation pathways and 2) 33 β (0.514 ± 0.0003) and 36 β (1.90 ± 0.002) values that are closer to the mass dependent values (0.515 and 1.89 respectively) than those reported for the other oxidation pathways. This implies that the NO2 oxidation pathway cannot explain the extreme Δ 33 S-values measured in urban aerosols. Our data show that if atmospheric SO2 oxidation by NO2 is neglected, both the O2 +TMI and OH oxidation pathways would be overestimated in urban areas. Finally, we conclude that another oxidation reaction is responsible for the high Δ 33 S-values measured in urban aerosol samples. Graphical abstract: Highlights: Atmospheric SO2 oxidation by NO2 cannot explain mass-independent fractionation of sulfur isotopes measured in urban aerosols. Neglecting the NO2 oxidation pathway leads to overestimate SO2 oxidation by O2 +TMI and OH. SO2 oxidation by NO2 presents a cross-over.